Osteoporosis in Lung Transplantation Candidates: Association With 6-minute Walking Test and Body Mass Index - AŞICIOĞLU, EBRU (ELSEVIER SCIENCE INC, 2016)
Background. Osteoporosis is a well-recognized complication in lung transplantation because of steroid use and immobilization. The aim of the study was to assess the prevalence of osteoporosis and risk factors associated with osteoporosis in lung transplantation candidates. Methods. The bone mineral density of 174 patients with various end-stage lung diseases was assessed at the pretransplantation period. Osteoporosis risk factors were analyzed with the consideration to principal diagnosis, demographic, and clinical parameters of lung disease, lung function tests and mobility test (6-minute walking test). A multivariate analysis was conducted to determine various demographic and clinical risk factors associated with bone mass loss in the pretransplant period. Results. The prevalence of osteoporosis and osteopenia was 46% and 35%, respectively, in the study population. Osteoporotic patients have lower body mass index and lower 6 minute walking distance than patients without osteoporosis. In addition, they have higher pulmonary artery pressure and history of noninvasive mechanical ventilation than in patients without osteoporosis. There was a significant negative correlation between the 6-minute walking test, body mass index, and the presence of osteoporosis in the study population. Multivariate logistic regression analysis confirmed that 6-minute walking test (odds ratio, 0.996) and body mass index (odds ratio, 0.847) were significantly and negatively correlated with the presence of osteoporosis. Conclusions. A significant proportion of patients with end-stage lung diseases have osteopenia or osteoporosis pretransplantation. This is the first study to demonstrate that 6-minute walking distance and bone mineral density independently predict osteoporosis in lung transplant candidates.
Keywords: PHYSICAL-ACTIVITY; RISK; MORTALITY; DENSITY; COPD